If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4 + 4x + 9 = 10x + 3 Reorder the terms: 4 + 9 + 7x + 4x = 10x + 3 Combine like terms: 4 + 9 = 13 13 + 7x + 4x = 10x + 3 Combine like terms: 7x + 4x = 11x 13 + 11x = 10x + 3 Reorder the terms: 13 + 11x = 3 + 10x Solving 13 + 11x = 3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13 + 11x + -10x = 3 + 10x + -10x Combine like terms: 11x + -10x = 1x 13 + 1x = 3 + 10x + -10x Combine like terms: 10x + -10x = 0 13 + 1x = 3 + 0 13 + 1x = 3 Add '-13' to each side of the equation. 13 + -13 + 1x = 3 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 3 + -13 1x = 3 + -13 Combine like terms: 3 + -13 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x | | x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 | | 3.2/16= | | (3x-4w)(5x-8w)= | | 8-4x=9-5x | | p=-3q+1 | | -3(4-3y)=3y+6 | | 2(6x+8)-5=12x+11 | | (2+3)x(3+3)=x | | 0.51m+0.03=0.4m-0.74 | | -7(k-1)-5=-2(k-6) | | 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 |